2022
DOI: 10.1186/s13568-022-01459-x
|View full text |Cite|
|
Sign up to set email alerts
|

Improving carboxymethyl cellulose edible coating using ZnO nanoparticles from irradiated Alternaria tenuissima

Abstract: In this paper, gamma-irradiation was successfully used to intensify the yield of Zinc oxide nanoparticles (ZnONPs) produced by the fungus Alternariatenuissima as a sustainable and green process. The obtained data showed that 500 Gy of gamma-irradiation increased ZnONPs’ yield to approximately four-fold. The synthesized ZnONPs were then exploited to develop active Carboxymethyl Cellulose films by casting method at two different concentration of ZnONPs 0.5% and 1.0%. The physicochemical, mechanical, antioxidant,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Fungal spores from the cultures (7 days old) of A. tenuissima were harvested and the spore concentration was adjusted to a concentration of 10 6 spores/ml. Spore suspension was transferred in vial sealed with paraffin and irradiated by gamma rays at a dose of 500 Gy, the best irradiation dose for maximum synthesis of ZnONPs 23 . Irradiation process was carried out at the Nuclear Research Center (Cairo, Egypt) using 60 Co Gamma chamber, MC20, Russia, with an average dose rate of 605.726 Gy h −1 at the time of the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Fungal spores from the cultures (7 days old) of A. tenuissima were harvested and the spore concentration was adjusted to a concentration of 10 6 spores/ml. Spore suspension was transferred in vial sealed with paraffin and irradiated by gamma rays at a dose of 500 Gy, the best irradiation dose for maximum synthesis of ZnONPs 23 . Irradiation process was carried out at the Nuclear Research Center (Cairo, Egypt) using 60 Co Gamma chamber, MC20, Russia, with an average dose rate of 605.726 Gy h −1 at the time of the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…1 C) showed that the crystal structure was hexagonal with a lattice parameter of 0.323110 nm which is in agreement with JCPDS card No. 361451 4 , 21 , 30 . It is noteworthy that, all the myco-fabricated NPs are pure and of a single phase (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To induce mutants with improved productivities of CoFeNPs, SeNPs, and ZnONPs, spore suspensions of Monascus purpureus ATCC16436 and Alternaria tenuissima AUMC10624 were separately prepared. According to previous studies 2 , 3 , 21 , 1000 Gy (for CoFeNPs and SeNPs) and 500 Gy (ZnONPs) of gamma rays were the most proper doses for maximum production of these NPs, so we used the same irradiation doses in this paper to isolate mutant strains with improved productivities. The irradiation process was performed using a 60 Co Gamma chamber (MC20, Russia) at the Nuclear Research Center, Egyptian Atomic Energy Authority.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports concluded the effect of gamma rays as an energetic ionizing radiation in induction of mutations in the exposed cells (Thacker 1999) through the repair mechanism in genes of the DNA of the irradiated cells (Ismaiel et al 2014(Ismaiel et al , 2015Zaki et al 2020;Zaki and El-Sayed 2021). Generally, exposure to physical mutagens such as gamma rays is a successful strategy to improve microbial strains by developing overproducers (Parekh et al 2000) with intensified production rates (El-Sayed et al 2020a, c;Zaki et al 2020) with industrial applications thereby effectively lowering the overall cost of the process, as supported by several reports (Anwar et al 2022;El-Sayed et al 2020d, e, f;El-Sayed 2021;El-Sayed et al 2022b;c).…”
Section: Discussionmentioning
confidence: 97%